Explanation:
see the above attachment to solve the question and get the answer.
hope this helps you.
Answer:

Explanation:
Change in velocity considering the x component will be
Final velocity-Initial velocity

Change in velocity considering the y component will be
Final velocity-Initial velocity

Resultant change in velocity
Acceleration= change in velocity per unit time hence

the answer is concave lens
Entropy measures disorder and nothing else
Answer:
A.B = -38
Explanation:
A = 2i + 9j and B = -i - 4j.
So, A.B = (2i + 9j).(-i - 4j)
= 2i.(-i) + 2i.(-4j) + 9j.(-i) + 9j.(-4j)
= -2i.i - 8i.j - 9j.i - 36j.j
since i.i = 1, j.j = 1, i.j = 0 and j.i = 0, we have
A.B = -2(1) - 8(0) - 9(0) - 36(1)
A.B = -2 - 0 - 0 - 36
A.B = -38